Effectiveness of trichloroacetic acid versus electrocautery for the treatment of anal high-grade squamous intraepithelial lesions in persons with HIV - Burgos, Joaquin; Curran, Adrià; Garcia, Jorge; Landolfi, Stefania; Hernández-Losa, Javier; Suanzes, Paula; Navarro, Jordi; Falcó, Vicenç (Infectious diseases (London, England), 2024)
This study aimed to compare trichloroacetic acid (TCA) versus electrocautery (ECA) for the treatment of anal high-grade squamous intraepithelial lesions (HSIL). This is an observational, single-center study. All subjects with HIV who had anal HSIL treated with TCA or ECA from 2010 to 2022 were included. Effectiveness was evaluated by on-treatment analysis, defining response as the resolution of HSIL and recurrence as a new diagnosis of HSILs during follow-up. A propensity score analysis was used to adjust for confounding factors. In total, 227 and 260 HSIL episodes were treated with ECA and TCA, respectively. Response was observed in 61.7% (95% CI: 55.3-68) of cases treated with ECA and in 73.1% (95% CI: 67.8-78.5) with TCA ( = .004). The effectiveness of TCA was higher in large and multifocal HSILs. Side effects were common with both treatments, but no serious events were described. Tolerability was good in 77.1% and 80.7% of patients treated with ECA and TCA, respectively. At 24 months, recurrent HSIL were observed in 36.3% (95% CI: 27.3-45) and 28% (95% CI: 20.2-35.8) in the ECA and TCA groups ( = .049). A nadir CD4 cell count ≤200 cells/µl was found to be a risk factor for recurrence (OR: 1.77; 95% CI: 1.12-2.78). In this study, treatment with TCA showed high effectiveness, low recurrence and good tolerability. Considering the benefits of TCA, it could be considered one of the first-line treatments for anal HSIL.